Pursuing the evolutionary agenda in economics and management research - Sidney G. Winter (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This essay first reviews what Nelson and Winter were trying to accomplish when they put forward An Evolutionary Theory of Economic Change (Belknap Press, Harvard, 1982). It then does a fast-forward to controversies and contributions in the recent past, and speculates on where the intellectual enterprise might be headed from here. The issues involved in the original motivations are definitely alive and well. Aside from the review of the basic issues behind the NW project, an important theme here is that an evolutionary approach to economics entails a degree of engagement with the realities of business organization and the quest for profit that has no parallel in mainstream economics. Thus it makes sense in retrospect that the evolutionary program has proved more influential in other research fields, including strategic management, technology studies and organization theory, than it is in economics proper. Recent controversies underscore the continuing existence of a challenging research agenda featuring the interactions among the dynamic processes at different levels - individuals, firms and market environments.
Keywords: 330